Evaluation of the architectural meaning of adapting traditional houses to become homestays in cultural heritage areas - Sumardiyanto, Bonifasius; Marsonia, Cecillia Diana Lelyta (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Slums are one of the threats to Cultural Heritage Areas (KCB) which consist of traditional houses, especially those with living museum status such as KCB Kotagede in Yogyakarta. One of the main causes of slums is the inability of the owner (heir) to provide funds to preserve the building, which requires large costs. Assistance from the government or other parties, which is often incidental, is not a sustainable solution. For this reason, efforts are needed to optimize the potential of KCB so that it can generate sustainable conservation costs. One effort is to adapt traditional houses into homestays that offer cultural experiences for tourists. The study was carried out in 4 (four) residential buildings which were selected using purposive sampling. The study method begins with identifying initial plans of traditional houses and identifying plans for developing adapted designs. Next, using the Form - Function - Meaning structural approach, an analysis was carried out to what extent the architectural meaning of a traditional house was maintained in its adaptation into a homestay. This study reveals that the adaptation of a traditional house into a homestay can be done while maintaining its architectural meaning.